(untitled) - Figler, Howard E. (Berkeley, CA., 2007)
With more than sixty-five combined years of experience in the career development field, Howard Figler and Richard Nelson Bolles are the undisputed authorities when it comes to helping people find meaningful work. In this revised and updated second edition of their classic guide for career counselors, Figler and Bolles show aspiring counselors how to break into the business, and give experienced counselors ideas for improving effectiveness and recharging their practice.
Keywords: Career development,Phát triển nghề nghiệp